My great-aunt Arizona - Houston, Gloria; Lamb, Susan Condie (New York, NY : HarperCollinsPublishers, 1992)
An Appalachian girl, Arizona Houston Hughes, grows up to become a teacher who influences generations of schoolchildren.
Keywords: Hughes, Arizona Houston, -- 1876-1969 -- Juvenile literature; Hughes, Arizona Houston, -- 1876-1969.; Teachers -- Appalachian Region -- Biography. -- Juvenile literature; Teachers